Регулирование свойств композиций на основе поливинилхлорида с использованием стабилизаторов, не содержащих свинец, для изоляции кабельной продукции - Золотарев, Владимир Михайлович; Чулеева, Елена Владимировна; Чулеев, Владимир Леонидович (НТУ "ХПИ", 2013)
Представлены результаты теоретических и экспериментальных исследований по регулированию свойств композиций на основе поливинилхлорида с использованием стабилизаторов, не содержащих свинец, для изоляции кабельной продукции. Определены основные закономерности теплофизических, физико-механических, электрофизических реологических характеристик при использовании комплексных систем Ca-Zn стабилизаторов изоляционных пластиков.

The paper presents results of theoretical and experimental research into controlling polyvinylchloride composition properties with application of lead-free stabilizers for cable products insulation. The basic regularities of thermal-physical, physicalmechanical, electrophysical, and rheological characteristics are revealed under utilization of complex Ca-Zn stabilizers of insulating elastrons.
PVC composition properties control with application of lead-free stabilizers for cable product insulation
Keywords: кабельная промышленность; пластикаты; кальций-цинковые стабилизаторы; изоляция; PVC compounds; insulation; temperature of glass transition; temperature of fragility